Extending UTAUT3 with Sharia value to predict SOTS adoption among Gen Z - Afifa, Ulfia Nur; Ratnasari, Ririn Tri (Jurnal Ekonomi & Keuangan Islam, 2026)
Purpose – This study analyzes the influence of behavioral intention and use behavior on the use of the Sharia Online Trading System (SOTS) among Generation Z investors in Indonesia by extending the UTAUT3 model through the Sharia value variable.Methodology– This study employed structural equation modeling (SEM) using SmartPLS 4.1 software. Data were collected from 250 Generation Z investors across Indonesia through a purposive random sampling technique based on specific criteria.Findings – Effort expectancy, price value, and Sharia value had a significant positive impact on behavioral intention. Similarly, habit, performance expectancy, sharia value, and effort expectancy significantly influenced use behavior. In contrast, social influence, facilitating conditions, and hedonic motivation did not significantly affect either intention or use behavior. Notably, there was an unexpected negative relationship between behavioral intention and use behavior, indicating a complex dynamic that requires further investigation.Implications – This study reinforces the UTAUT3 model within the context of sharia digital finance and emphasizes the importance of effort expectancy, price value, and religious compliance in driving adoption. From a practical perspective, SOTS providers should focus on enhancing effort expectancy and integrating Sharia values to attract young Muslim investors.Originality – Sharia values are integrated into the UTAUT3 model to examine Generation Z’s adoption of the Sharia Online Trading System (SOTS). This integration addresses a research gap concerning behavioral factors in Sharia fintech within emerging markets.